2022
DOI: 10.3390/foods11142057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biogenic Amine-Degrading Lactobacillus on the Biogenic Amines and Quality in Fermented Lamb Jerky

Abstract: This study compares five types of lamb jerky, namely, CO (without starter culture), PL-4 (with producing putrescine, cadaverine, histamine, and tyramine), BL4-8 (degrading putrescine, cadaverine, histamine, and tyramine), CL4-3 (degrading putrescine and tyramine), and X3-2B (degrading histamine and tyramine). A study was performed to examine the effects of starter culture on the physical–chemical quality, flavor, and biogenic amines (BAs) during fermentation and ripening. At the end of fermentation, the pH val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…This phenomenon can be attributed to the elevated roasting temperature, which led to an increase in both the b* and L* values, resulting in an overall decline in the E* value. These results are consistent with the findings of Sun et al [3], highlighting the ability of x3-2b bacterial powder prepared using composite protective agents to effectively enhance the color of fermented lamb jerky.…”
Section: Effects Of X3-2b Bacterial Powder On Ph Water Activity (A W ...supporting
confidence: 93%
See 3 more Smart Citations
“…This phenomenon can be attributed to the elevated roasting temperature, which led to an increase in both the b* and L* values, resulting in an overall decline in the E* value. These results are consistent with the findings of Sun et al [3], highlighting the ability of x3-2b bacterial powder prepared using composite protective agents to effectively enhance the color of fermented lamb jerky.…”
Section: Effects Of X3-2b Bacterial Powder On Ph Water Activity (A W ...supporting
confidence: 93%
“…The fermented lamb jerky particles were evenly spread on the bottom of a measurement dish, and the a w value was measured using an automatic water activity meter (WA-160A, Decagon, Pullman, WA, USA). A TPC automatic colorimeter (Olympus Optics, Beijing, China) was used to measure the differences in color from the reference E* values for analysis and evaluation, calculated by the formula: E* = a*/L* + a*/b* [3].…”
Section: Determination Of the Physical And Chemical Indicators Of Fer...mentioning
confidence: 99%
See 2 more Smart Citations
“…A study based on 16S rRNA gene amplicon sequencing found that the microbial composition of pork may be similar at different storage temperatures, broadening the knowledge of microbial changes that may occur during the storage, transportation or retail of pork [5]. Qiu et al [6] explored changes in the bacterial community during the storage of ready-to-eat chicken meat and found that pathogenic bacteria and/or spoilage bacteria directly interact, and, during storage at 4 and 22 • C, Enterobacter was dominant in microbial interactions, whereas Pseudomonas was dominant so at 22 • C. Researchers have been actively working to slow down the spoilage process of food from various aspects, such as the use of atmosphere packaging [7], the use of vacuum packaging [8], the addition of preservatives [9,10] and the addition of starter cultures [11]. However, these external treatments to slow down spoilage may lead to the simultaneous destruction of food quality characteristics and flavor, which can negatively affect consumer acceptability.…”
mentioning
confidence: 99%